THE USE OF MOSSBAUER SPECTROSCOPY IN STABLE ISOTOPE GEOCHEMISTRY - Polyakov V.B.; Mineev S.D. (My University, 2000)
The use of Mössbauer spectroscopic data on the second-order Doppler (SOD) shift to determine the reduced isotopic partition function ratio (β-factor) has been considered by the example of iron. Using the relation between the β-factor and the SOD shift in Mössbauer spectra, the temperature dependence of the iron β-factors for a wide range of minerals has been evaluated from experimental data on the SOD shift. It is shown that the β-factors of Fe³⁺ ions are considerably higher than those of Fe²⁺. The curve describing the temperature dependence of the β-factor for native iron is the boundary separating fields that are typical for ferric and ferrous ions. The value of the iron β-factor increases with increasing covalence of chemical bonds. In the case of covalent chemical bonds, the iron β-factor achieves high values even for ferrous compounds.